การเปรียบเทียบการส่งสินค้าอาหารสดผ่านศูนย์กระจายสินค้ากับการส่งโดยตรงสู่ร้านค้า: กรณีนำร่องของบริษัทค้าปลีกสมัยใหม่ - ปภาวรินทร์ ทะสอน (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
The purpose of this individual study was to study about the processing of transportation goods into distribution center and direct store delivery. This study was collected from operation data and office workers interviewing. Therefore, following each two processing by stimulated the cost analysis which effected to quality cost and timing. Then, comparing the data of DSD and CD processing of pilot supplier cases and present the method to develop the delivery policy of suppliers. The finding of this individual study found 4 aspects of the decision for delivery as following; 1) The cost of DSD was higher than CD at least four-five times. 2) The distances of DSD were less than CD equal to 16.64 hours. 3) The weight per cycle of delivery were average 300-350 kilograms per trucks 4) The quality of products when delivering to retailer store must be fresher than that delivered by CD.